EFEKTIVITAS PBL BAHASA INDONESIA UNTUK KREATIVITAS LITERASI SISWA SMAN 11 MAROS - Ince Nasrullah; Irwan Fadli; Aryanti; Nur Ilmi; Nurul Hikmah; Sariani; Abdillah Hafid Burhami (PT. CASA CENDEKIA MEDIA, 2025)
This community service program aimed to enhance students’ creativity through the implementation of Project-Based Learning (PBL) in Indonesian language learning at SMAN 11 Maros. The activity, conducted on October 30, 2025, involved 35 students and was organized in the form of a seminar and discussion on the application of project-based approaches in writing short stories themed around local wisdom. Using descriptive qualitative methods, the program focused on introducing PBL concepts, stages, and benefits for developing creative writing skills. The findings indicated significant improvement in students’ active participation, creative thinking, and writing quality. Students were able to integrate elements of local culture, such as traditions and folklore, into original literary works. Moreover, the project encouraged collaboration, critical thinking, and self-confidence. In conclusion, project-based learning serves as a relevant pedagogical strategy to strengthen literacy, creativity, and cultural identity among Indonesian students